Robust mechanical stability, electronic structure, magnetism and thermoelectric properties of CoFeMnSb quaternary Heusler alloy: A first principle study - Enamullah; Lee, Seung-Cheol (Elsevier BV, 2018)
Mechanical, structural, electronic, magnetic and thermoelectric properties of multi functional CoFeMnSb quaternary Heusler alloy have been studied using spin polarized Density Functional and semiclassical Boltzmann transport theory. Ab-initio study reveals halfmetallic ferromagnetic characteristics of the alloy leading to high spin polarization. The calculated value of total magnetic moment (m(t) = 4.99 mu(B)) almost follow the Slater-Pauling rule which is another prerequisite of halfmetallicity. Study of hydrostatic pressure shows a significant effect on the electronic structure of the alloy however, along with the robust mechanical stability there is no magnetic phase transition seen as such in the whole range of pressure. Due to the occurrence of flat bands near the Fermi level(E-F) in the minority spin channel, thermoelectric properties are also studied for both the spin polarized channel using BoltzTraP code under constant relaxation time approximation of the charge carriers. Halfmetallic properties, robust mechanical stability and significantly high value of Seebeck coefficient (similar to 800 mu V/K for p-type and similar to -900 mu V/K for n-type) makes the material promising for spintronic as well as thermoelectric applications. (c) 2018 Published by Elsevier B.V.